Effectiveness and Safety of Anti-Tumor Necrosis Factor-Alpha Agents Treatment in Behcets' Disease-Associated Uveitis: A Systematic Review and Meta-Analysis - Yunwei Hu; Zhaohao Huang; Shizhao Yang; Xiaoqing Chen; Wenru Su; Dan Liang (Frontiers Media S.A., 2020)
PurposeWe conducted a systematic review and meta-analysis to determine the effectiveness and safety of anti-tumor necrosis factor-alpha (TNF-α) agents in the treatment of Behcets' disease (BD)-associated uveitis.MethodThree electronic databases, Embase, MEDLINE, and the Cochrane Library, were searched for eligible papers focusing on the anti-TNF-α agents treatment in BD-associated uveitis with at least 6 months follow-up time. A systematic review and meta-analysis was conducted on selected papers with appropriate clinical and methodological homogeneity. The effectiveness outcomes included inflammation remission, visual acuity (VA) improvement, central macular thickness (CMT) decrease, corticosteroid (CS)-sparing effects, and the safety outcomes included minor and severe drug-related adverse events (AEs).ResultFrom Jan 2010 to Dec 2019, there were 504 records produced in total, in which 18 clinical trials were selected for meta-analysis (15 trials were retrospective studies, and 3 were prospective studies). The number of patients in each study ranged from 11 to 163 and the mean follow-up time from 0.9 to 6.44 years. During the follow-up, the pooled inflammation remission rate was 68% with a 95% confidence interval (CI) of 0.59-0.79, VA improvement rate was 60% (95% CI 0.47-0.77), CMT decrease was 112.70 μm (95% CI 72.8-153.0 μm). The proportions of patients who had CS-suspended and CS-tapered reached 38% (95% CI 0.23-0.65) and 34% (95% CI 0.16-0.70), respectively. The severe AEs were reported but not common, which included severe infusion reactions, pneumonia, bacteremia, tuberculosis, melanoma, and lymphoma.ConclusionAnti-TNF-α agents treatment has high effectiveness including efficient inflammation remission, satisfactory VA improvement, obvious CMT reduction, and significant CS-sparing effects. Although some drug-related AEs were reported, the incidence of severe AEs was acceptable. Anti-TNF-α agents treatment is a promising option for controlling BD-associated uveitis.